FEATURES OF THE INTRODUCTION OF A MODULAR LEARNING SYSTEM IN HIGHER EDUCATION - Sormonqulov Shavkatjon Rasulovich (Modern American Journals, 2025)
In this article, the concept of a modular learning system, the purpose, features of a modular learning system, special attention is paid to the components of the module. It also covers the introduction of a modular learning system in higher education in Uzbekistan. The content of modular learning technology in the given higher education system serves to achieve a deeper understanding of the essence.
Keywords: Higher education, student, factor, professionalism, module, modular system, learning process, independent research, project work, team task, case study, individual opportunity.